The Effect of Affirmation Relaxation Techniques on Anxiety Levels in Third-Trimester Pregnant Women - Nurhasanah; Triana Indrayani; Bunga Tiara Carolin (Health and Technology Journal (HTechJ), 2024)
Pregnancy is often found with psychological changes, one of which is anxiety; high anxiety can cause negative impacts in the form of labor pain and the occurrence of maternal and fetal mortality during the delivery process. To prevent and overcome anxiety can be overcome by affirmation relaxation. Relaxation affirmation combines breathing and the repetition of simple positive sentences carried out regularly to improve the condition of being relaxed and self-integrated and create good self-efficacy. This study aims to know the effect of affirmation relaxation techniques on anxiety levels in third-trimester pregnant women at Cibinong Health Center. This study used a pre-experiment with one group, and the pre-test-posttest design—data analysis was done using a paired T-test. Sample selection in this study used a purposive sampling technique, namely sample selection, so the sample amounted to 30 people. The average level of anxiety in third-trimester pregnant women before and after the intervention was based on statistical tests with paired sample t-tests with a value of p = 0.000 (p < 0.05). There is an effect of giving affirmation relaxation techniques to reduce anxiety levels in third-trimester pregnant women at the Cibinong-Bogor Health Center in 2023.